The inhibitory effects of zinc oxide nanoparticles on clinical isolates of Microsporum canis in dogs and cats - Masoomeh Khanipour Machiani; Shahram Jamshidi; Donya Nikaein; Alireza Khosravi; Asad Balal (Veterinary Medicine and Science, 2024)
Abstract Introduction Microsporum canis is the most common dermatophyte infecting pets and their owners, and its long duration of treatment and increasing rate of drug resistance have caused the attention of researchers to be directed towards the use of nanoparticles and new alternatives for treatment. This study investigated the antifungal effects of zinc oxide (ZnO) nanoparticles on clinical isolates of M. canis in dogs and cats and subtilisin 1 (SUB1) gene expression. Materials and methods Zinc oxide nanoparticles were prepared using the wet chemical method at a concentration of 4000 ppm. Its antifungal potential was evaluated at concentrations of 62.5–4000 ppm by disk diffusion and microdilution methods against 10 isolates of M. canis. The effect of this product on SUB1 gene expression was investigated by quantitative real‐time PCR method. Results The results of the disk diffusion test showed that the highest inhibitory diameter was at the highest concentration of ZnO nanoparticles (34 mm), and the inhibitory zone was observed in dilutions up to 250 ppm. The minimum inhibitory concentration (MIC) of ZnO nanoparticles was between 250 and 500 ppm, and the minimum fungicidal concentration was between 500 and 1000 ppm. There was a significant reduction in SUB1 gene expression in sub‐MIC concentration (125–250 ppm) (p < 0.05). Conclusion This study showed that ZnO nanoparticles have a concentration‐dependent inhibitory effect on M. canis. Moreover, ZnO nanoparticles could decrease the expression of SUB1, an enzyme involved in fungi adhesion to the epidermis. Nevertheless, more studies must be done in the future to determine the possible side effects and safety of ZnO nanoparticles along with their efficacy in vivo.